PENINGKATAN KINERJA MELALUI SERVANT LEADERSHIP, DISIPLIN KERJA DAN KEPUASAN KERJA PADA DINAS PERTANIAN KABUPATEN DEMAK - Evvien Akbar; Nurhidayati Nurhidayati (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2018)
This study aims to analyze the influence of servant leadership and work discipline on employeeperformance with job satisfaction as intervening variable. Population in this research is employeeswho work at Agriculture Department of Demak Regency for 121 employees, with total sampleof 55 employees. The sampling technique used in this study is Proportional Random Sampling.The analysis tool is the path analysis, where previously tested the validity and reliability as wellas the classical assumption test. Test results show that servant leadership and work disciplineproved to have a positive and significant impact on job satisfaction. Servant leadership provedto have a positive and significant influence on employee performance, can be interpreted thatthe higher servant leadership, the more leaders are able to serve their subordinates sincerely,so that it will have an impact on the high performance of employees. Work discipline proved tohave a positive and significant effect on employee performance. Job satisfaction has a positiveand significant effect on employee performance, meaning that the higher level of job satisfactionof employees, it will certainly have an impact on the high performance of employees.Keywords: Servant leadership, work discipline, job satisfaction and employee performance